“Variation” vs “individuality”: Redefinition in handwriting examination - Chang, Chih Yun (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The present article attempts to discuss the practical problems which have appeared in several recent cases, leading to converse conclusions and affecting the court trial as well as the rights and interests of the parties. The reinterpretation of “individuality” and “variation” can allow document examiners to use and interpret all the theoretical bases and methods of analysis, comparison, and judgment without any hesitation or uncertainty. It can also highlight the “basic theory” which must be applied differently depending on individual cases and in order to avoid analysis errors when non-professional document examiners reevaluate the same case.
Keywords: variation; individuality; handwriting examination; redefined theory; critical characteristics; results verification; reconstruction of document examination